(3eNJUQ JGQjN OeTb dGHf YSGcQs - (3eMeO Hf ecQe Hf Ydj, CHh GdaVd, LeGd GdOjf GHf efXhQ GdCfUGQj GdQhjaYj GdEaQjbj, J (B711 (3g` s; (3Ydj Hf GdMSf Hf gHI Gddg GdOeTbj , CHh GdbGSe, KbI GdOjf GHf YSGcQ,J (B600 (3g` s
(3ChdgG (B:s
(3ef LHjQ Hf eWYe s
(3BNQgG (B:s
(3Edi GdMSf Hf Ydi Hf THjH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B106s
Keywords: (3GdJGQjNs